2016
DOI: 10.1007/s11164-016-2526-7
|View full text |Cite
|
Sign up to set email alerts
|

Detailed characteristics of adsorption of bisphenol A by highly hydrophobic MCM-41 mesoporous molecular sieves

Abstract: A surfactant structure-directing agent was used to synthesize a hydrophobic mesoporous material (MCM-41-d) at room temperature. As-prepared materials were characterized through X-ray diffraction (XRD) analysis, Fouriertransform infrared (FT-IR) spectroscopy, N 2 adsorption-desorption isotherm analysis, and thermogravimetry (TG). The properties of the samples for adsorption of bisphenol A (BPA) from water were also investigated in detail. The results revealed that pH affected BPA adsorption. Equilibrium and kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 27 publications
2
8
0
Order By: Relevance
“…A significant reduction in the surface area and pore volume were observed, probably due to the almost complete filling of the pores with amine functional groups. Similar results were found by Liu et all (2016), working with highly hydrophobic MCM-41 mesoporous molecular sieves [27]. The mesoporous silica R1a (Figure S2) X-ray analysis is characteristic of a material with hexagonal channel order, which is consistent with that obtained by Beck et al [28].…”
Section: Characterization Of Mesoporous Silica Materialssupporting
confidence: 89%
“…A significant reduction in the surface area and pore volume were observed, probably due to the almost complete filling of the pores with amine functional groups. Similar results were found by Liu et all (2016), working with highly hydrophobic MCM-41 mesoporous molecular sieves [27]. The mesoporous silica R1a (Figure S2) X-ray analysis is characteristic of a material with hexagonal channel order, which is consistent with that obtained by Beck et al [28].…”
Section: Characterization Of Mesoporous Silica Materialssupporting
confidence: 89%
“…It could be observed that IM0.05 could adsorb BY28 efficiently even after reusing for three times. The removal percentage somewhat diminished from 88.23% in the first cycle to 78.65% in the third cycle, perhaps because during the recycling experiments, a slight remnant of the BY28 dye still existed on the IM0.05 surface [94]. Overall, the IM0.05 Table 4 Kinetic parameters for BY28 adsorption on IM0.05…”
Section: Recovery and Regeneration Of Adsorbentmentioning
confidence: 99%
“…As showed in Table 2 , the pseudo‐second‐order model, according to the R 2 value, was more appropriate for the CAPE bindings onto all the composites. The k 2 for the HKUST‐1@LC‐MIP [(0.33 ± 0.03) × 10 −3 g µmol −1 min −1 ] was higher than that of HKUST‐1@LC‐free MIP [(0.20 ± 0.01) × 10 −3 g µmol −1 min −1 ], indicating that the rate‐limiting step of controlling binding process of CAPE might not be chemisorption …”
Section: Resultsmentioning
confidence: 99%
“…The k 2 for the HKUST-1@LC-MIP [(0.33 ± 0.03) × 10 −3 g µmol −1 min −1 ] was higher than that of HKUST-1@LC-free MIP [(0.20 ± 0.01) × 10 −3 g µmol −1 min −1 ], indicating that the rate-limiting step of controlling binding process of CAPE might not be chemisorption. [51]…”
Section: Adsorption Isotherms and Kinetics Of Cape On Hkust-1@lc-mipmentioning
confidence: 99%